Timing Tax Evasion - Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2004)
Standard models of tax evasion implicitly assume that evasion is either fully detected, or not detected at all. Empirically, this is not the case, casting into doubt the traditional rationales for interior evasion choices. I propose two alternative, dynamic explanations for interior tax evasion rates: Fines depending on the duration of an evasion spell, and different vintages of income sources subject to aggregate risk and fixed costs when switched between evasion states. The dynamic approach yields a transparent representation of revenue losses and social costs due to tax evasion, novel findings on the effect of policy on tax evasion, and a tractable framework for the analysis of tax evasion dynamics.
Keywords: E6; H2; 330; Dynamic tax evasion; detection risk; duration dependent fine; inaction range; optimal taxation; Steuervermeidung; Konsumentenverhalten; Risikopräferenz; Dynamische Optimierung; Theorie